Markedly different genome arrangements between serotype a strains and serotypes b or c strains of Aggregatibacter actinomycetemcomitans - Kittichotirat Weerayuth; Bumgarner Roger; Chen Casey (BMC Genomics, 2010)
Abstract Background Bacterial phenotype may be profoundly affected by the physical arrangement of their genes in the genome. The Gram-negative species Aggregatibacter actinomycetemcomitans is a major etiologic agent of human periodontitis. Individual clonal types of A. actinomycetemcomitans may exhibit variable virulence and different patterns of disease association. This study examined the genome arrangement of A. actinomycetemcomitans using the genome sequences of serotypes a-c strains. The genome alignment and rearrangement were analyzed by the MAUVE and the GRIMM algorithms. The distribution patterns of genes along the leading/lagging strands were investigated. The occurrence and the location of repeat sequences relative to the genome rearrangement breakpoints were also determined. Results The genome arrangement of the serotype a strain D7S-1 is markedly different from the serotype b strain HK1651 or the serotype c strain D11S-1. Specific genome arrangements appear to be conserved among strains of the same serotypes. The reversal distance between D7S-1 and HK1651 by GRIMM analysis is also higher than the within-species comparisons of 7 randomly selected bacterial species. The locations of the orthologous genes are largely preserved between HK1651 and D11S-1 but not between D7S-1 and HK1651 (or D11S-1), irrespective of whether the genes are categorized as essential/nonessential or highly/nonhighly expressed. However, genome rearrangement did not disrupt the operons of the A. actinomycetemcomitans strains. A higher proportion of the genome in strain D7S-1 is occupied by repeat sequences than in strains HK1651 or D11S-1. Conclusion The results suggest a significant evolutionary divergence between serotype a strains and serotypes b/c strains of A. actinomycetemcomitans. The distinct patterns of genome arrangement may suggest phenotypic differences between serotype a and serotypes b/c strains.